2023
DOI: 10.3390/plants12030643
|View full text |Cite
|
Sign up to set email alerts
|

Community Profiling of Seed Endophytes from the Pb-Zn Hyperaccumulator Noccaea caerulescens and Their Plant Growth Promotion Potential

Abstract: Endophytes within plants are known to be crucial for plant fitness, and while their presence and functions in many compartments have been studied in depth, the research on seed endophytes is still limited. This work aimed to characterize the seed endophytic and rhizospheric bacterial community of two Noccaea caerulescens Pb-Zn hyperaccumulator populations, growing on two heavy-metal-polluted sites in Belgium. Cultured representatives were evaluated for their potential to enhance seed germination and root lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…The results reported by Langill et al [18] demonstrated that the selection of the core seed endophytic microbiome is crucial for host-plant fitness, highlighting the precarious symbiotic relationship it has with both the plant and seed. They hypothesized that introducing seed endophytes from N. caerulescens to the seeds of A. thaliana would improve the germination and overall plant health and biomass when A. thaliana is forced to germinate in marginal conditions.…”
Section: An Overview Of This Special Issue's Articlesmentioning
confidence: 99%
“…The results reported by Langill et al [18] demonstrated that the selection of the core seed endophytic microbiome is crucial for host-plant fitness, highlighting the precarious symbiotic relationship it has with both the plant and seed. They hypothesized that introducing seed endophytes from N. caerulescens to the seeds of A. thaliana would improve the germination and overall plant health and biomass when A. thaliana is forced to germinate in marginal conditions.…”
Section: An Overview Of This Special Issue's Articlesmentioning
confidence: 99%
“…Understanding the functional significance of seed endophytes has gained prominence due to their potential contributions to plant health and productivity. Numerous studies have revealed the ability of seed endophytes to enhance nutrient acquisition [7], improve stress tolerance [4,8], and promote plant growth [9,10]. These beneficial effects are attributed to various mechanisms, including nitrogen fixation, phosphate solubilization, production of plant-growth-promoting substances, and modulation of the plant's immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Noccaea caerulescens, a hyperaccumulator plant species, has garnered significant importance in the field of phytoremediation and ecological research, making it an ideal candidate for our resilient plant. This metallophyte exhibits an exceptional tolerance to and accumulation of heavy metals, particularly zinc, cadmium, and nickel, in its aboveground tissues [10]. Still, this plant is not only found in polluted areas but also has a strong presence in dry hillside meadows, gardens, bare ground, and forests [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations